1977
DOI: 10.1111/j.1432-1033.1977.tb11748.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Electrochemical Proton Gradient by Nitrate Respiration in Membrane Vesicles from Anaerobically Grown Escherichia coli

Abstract: In membrane vesicles, isolated from Escherichia coli ML 308-225, grown anaerobically on glucose in the presence of nitrate, nitrate respiration results in the generation of a membrane potential, A$, as indicated by the accumulation of the lipophilic cation triphenylmethylphosphonium, and a transmembrane pH gradient, dpH, as indicated by the accumulation of the weak acid acetate in flow dialysis experiments.Under anaerobic conditions, and low concentrations of formate, the electrochemical proton gradient, Ap"+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 32 publications
(28 reference statements)
1
30
0
Order By: Relevance
“…No active transport system for this monocarboxylic acid was detectable in vesicles of oxalateor formate-grown Pseudomonas oxalaticus. It has been shown in E. coli and Bacillus subtilis that formate is taken up by simple diffusion of the undissociated molecule (Garland et al, 1975;Boonstra and Konings, 1977). This is most likely also the situation in P. oxalaticus.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…No active transport system for this monocarboxylic acid was detectable in vesicles of oxalateor formate-grown Pseudomonas oxalaticus. It has been shown in E. coli and Bacillus subtilis that formate is taken up by simple diffusion of the undissociated molecule (Garland et al, 1975;Boonstra and Konings, 1977). This is most likely also the situation in P. oxalaticus.…”
Section: Discussionmentioning
confidence: 88%
“…Garland et al (1975) concluded from their experiments with Escherichia coli that formate enters the cell by simple diffusion. This is also the case with acetate (Padan et al, 1976;Boonstra and Konings, 1977). Nothing is known about the uptake of carbon sources such as oxalate, glyoxylate or glycollate, particularly with respect to the requirement for metabolic energy and the involvement of specific carrier systems.…”
mentioning
confidence: 99%
“…In the assimilatory process, which may occur aerobically or anaerobically, nitrate is ultimately reduced to ammonia (NH 3 ) and subsequently incorporated into biomass. This pathway is performed by many bacteria, fungi, and plants.…”
mentioning
confidence: 99%
“…The enzymes for this pathway are found only in bacteria. Two main forms have been described so far, and in both, nitrate reduction is coupled to the generation of a proton motive force (3,17), which is directly utilized as a source of energy or transformed into ATP by a membrane-associated ATPase. In one form, reported for Escherichia coli and other members of the family Enterobacteriaceae, the organisms reduce nitrate to nitrite, which is then excreted or further reduced to NH 3 by a dissimilatory (e.g., in E. coli [25]) or assimilatory nitrite reductase.…”
mentioning
confidence: 99%
“…Moreover, studies with intact cells (9) and this in vitro system (7,(10)(11)(12)(13)(14) provide virtually unequivocal evidence for the central obligatory role of chemosmotic phenomena in active transport. Recent evidence with isolated membrane vesicles (15,16) indicates that carriermediated lactose efflux down a concentration gradient is an ordered mechanism in which lactose is released first from the carrier, followed by loss of a proton, and that the unloaded carrier may be negatively charged.…”
mentioning
confidence: 99%